3 Different Types of Strength Training in Older Women - Correa, C. S.; LaRoche, D. P.; Cadore, E. L.; Reischak-Oliveira, A.; Bottaro, M.; Kruel, L.F. M.; Tartaruga, M. P.; Radaelli, R.; Wilhelm, E. N.; Lacerda, F. C.; Gaya, A. R.; Pinto, R. S. (International Journal of Sports Medicine, 2012)
The objective of the present study was to evaluate and compare the neuromuscular, morphological and functional adaptations of older women subjected to 3 different types of strength training. 58, healthy women (67±5 year) were randomized to experimental (EG, n=41) and control groups (CG, n=17) during the first 6 weeks when the EG group performed traditional resistance exercise for the lower extremity. Afterwards, EG was divided into three specific strength training groups; a traditional group (TG, n=14), a power group (PG, n=13) that performed the concentric phase of contraction at high speed and a rapid strength group (RG, n=14) that performed a lateral box jump exercise emphasizing the stretch-shortening-cycle (SSC). Subjects trained 2 days per week through the entire 12 weeks. Following 6 weeks of generalized strength training, significant improvements occurred in EG for knee extension one-repetition (1RM) maximum strength (+19%), knee extensor muscle thickness (MT, +15%), maximal muscle activation (+44% average) and onset latency ( − 31% average) for vastus lateralis (VL), vastus medialis (VM) and rectus femoris (RF) compared to CG (p<0.05). Following 6 more weeks of specific strength training, the 1RM increased significantly and similarly between groups (average of +21%), as did muscle thickness of the VL (+25%), and activation of VL (+44%) and VM (+26%). The onset latency of RF (TG=285±109 ms, PG=252±76 ms, RG=203±43 ms), reaction time (TG=366±99 ms, PG=274±76 ms, RG=201±41 ms), 30-s chair stand (TG=18±3, PG=18±1, RG=21±2) and counter movement jump (TG=8±2 cm, PG=10±3 cm, RG=13±2 cm) was significantly improved only in RG (p<0.05). At the end of training, the rate of force development (RFD) over 150 ms (TG=2.3±9.8 N·s − 1, PG=3.3±3.2 N·s − 1, RG=3.8±6.8 N·s − 1, CG=2.3±7.0 N·s − 1) was significantly greater in RG and PG than in TG and CG (p<0.05). In conclusion, rapid strength training is more effective for the development of rapid force production of muscle than other specific types of strength training and by consequence, better develops the functional capabilities of older women.
Keywords: rapid strength training; elderly women; functional capacity; reaction time; muscle thickness